PENGARUH TANGIBILITY, PROFITABILITAS, GROWTH, RISIKO BISNIS DAN LIKUIDITAS TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI KIMIA DAN DASAR YANG TERDAFTAR DI BEI PERIODE 2011-2015 - Arfina, Winda; Rokhmawati, Andewi; Efni, Yulia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The study aims to determine the effect tangibility, profitability, growth,business risk and liquidity on debt policy with size and age of the company as control variables at the chemical industry and basic manufacturing sector period 2011-2015. The data used for this study were secondary data from financial statements. The sampling technique used was purposive sampling, which obtained 56 samples of firm that fitted the sample criteria. The method of analysis used was multiple regression analysis. In this study, the independent variable is tangibility (X1), profitability (X2), growth (X3), business risk (X4), liquidity (X5), variable control firm size (X6) and firm age (X7) while the dependent variable is debt policy (Y). Based on the test result, simultaneously test show that tangibility,growth, business risk, liquidity, size and firm age had a significant effect on debt policy. Mean while partially test tangibility has a positive effect on debt policy without control variables however has no effect but has positive direction, profitability, business risk and liquidity have negatively significant on debt policy after and before the control variables are entered. Growth does not has an effect but has a positive direction on the debt policy after and before the control variables are included, while control variables size positively affect the debt policy, and the age of the company does not affect the debt policy.Keywords: Tangibility, Profitability, Growth, Business Risk, Liquidity, Firm Size, Firm Age, and Debt Policy.